Padronização das técnicas de transplante de espermatogônias em Zebrafish (Danio rerio) e utilização desta espécie como modelo experimental para se investigar a biologia das espermatogônias tronco em teleósteos - Rafael Henrique Nobrega (2011)
Spermatogenesis is a complex cellular developmental process, in which a small population of spermatogonial stem cells (SSCs) generates a large number of spermatozoa that act as genome vectors by propagating a species. In many species, the spermatogenic process occurs continuously or repeatedly during the adult male lifespan due to the capability of the SSCs to either self-renewal to maintain their number, or to differentiate into daughter cells that eventually will form spermatozoa. The proper balance between these two pathways is crucial for the spermatogenic homeostasis, and this balance is tightly regulated in the specific regions of the seminiferous tubules that house the SSCs, which are referred to as stem cell niche. Since the biological properties of SSCs are unknown for several species, the present study first aimed at characterizing the SSCs and their niche in zebrafish (Danio rerio) by morphological and functional means. Subsequently, we aimed at developing a SSC transplantation technique for this species. Two populations of single spermatogonia (Aund* and Aund) were identified in zebrafish testis as candidate SSCs. Using vasa::egfp transgenic zebrafish and stem cell properties, such as to retain a BrdU-label for extended periods of time, we have localized the SSC niche in zebrafish as being preferentially located close to the interstitial compartment. This suggests that hormones and/or paracrine factors from interstitial cells or molecules derived from the interstitial vasculature, might play important roles in the regulation of the SSC niche. Using SSC transplantation techniques, which were successfully developed and standardized in zebrafish, we have shown that germ cell fractions enriched in Aund* and Aund were able to colonize busulfan-depleted seminiferous tubules of recipient males and develop into cysts of type B spermatogonia and spermatocytes three weeks after transplantation. Moreover, type Aund spermatogonia differentiated into oocytes when transplanted into zebrafish ovaries. Therefore, we have shown both the stemness and the sexual plasticity of type Aund spermatogonia, and hence the presence of SSCs in this population of germ cells in the zebrafish testes. Hormonal and gene expression profiles from busulfan-depleted testes before transplantation indicate that higher androgen levels combined with the down-regulation of amh and up-regulation of igf3 (igf1b) might have created a particular environment (niche), in which the balance of signaling molecules was shifted towards favoring SSC differentiation over their self-renewal. This pro-differentiation condition might have influenced the fate of the donor SSC after transplantation. In summary, the present work suggests that zebrafish might represent an interesting model for studying the SSC cell biology in teleost fish.